2021
DOI: 10.5851/kosfa.2021.e41
|View full text |Cite
|
Sign up to set email alerts
|

Use of Green Tea Extract and Rosemary Extract in Naturally Cured Pork Sausages with White Kimchi Powder

Abstract: The impact of green tea extract powder and rosemary extract powder, alone or in combination, on the quality characteristics of naturally cured pork sausages produced with white kimchi powder as a nitrate source was evaluated. Ground pork sausages were assigned to one of seven treatments: control (0.01% sodium nitrite and 0.05% sodium ascorbate), treatment 1 (0.3% white kimchi powder and 0.05% green tea extract powder), treatment 2 (0.3% white kimchi powder and 0.1% green tea extract powder), treatment 3 (0.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…pH Nitrite sources (N) did not affect (p>0.05) the pH of pork products (Table 2), indicating that there were no significant (p>0.05) differences in pH between sodium nitrite-and radish powder-treated pork products (Table 3). These findings agreed with those reported by Sindelar et al (2007) and Yoon et al (2021), who found that pH of meat products naturally cured with celery juice powder and white kimchi powder, respectively, did not differ from those of meat products cured with sodium nitrite. In contrast, phosphate replacements (P) was found to significantly (p<0.001) affect the pH of ground pork products (Tables 2).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…pH Nitrite sources (N) did not affect (p>0.05) the pH of pork products (Table 2), indicating that there were no significant (p>0.05) differences in pH between sodium nitrite-and radish powder-treated pork products (Table 3). These findings agreed with those reported by Sindelar et al (2007) and Yoon et al (2021), who found that pH of meat products naturally cured with celery juice powder and white kimchi powder, respectively, did not differ from those of meat products cured with sodium nitrite. In contrast, phosphate replacements (P) was found to significantly (p<0.001) affect the pH of ground pork products (Tables 2).…”
Section: Resultssupporting
confidence: 93%
“…Cooking yield was not affected (p>0.05) by nitrite sources (N) (Tables 2 and 3). Conversely, Yoon et al (2021) showed that pork sausages containing sodium nitrite showed a higher cooking yield than those containing white kimchi powder. However, Jeong et al (2020) found no significant difference in cooking yield between pork products cured with various vegetable powders (Chinese cabbage, radish, and spinach) and sodium nitrite-added products, consistently with the findings reported herein.…”
Section: Cooking Yieldmentioning
confidence: 96%
“…Pennyroyal (Mentha pulegium L.) powder when added to beef patties significantly reduced in lipid oxidation (Guliyeva and Turhan, 2021). Extracts from rosemary (rosmaridiphenol, rosmariquinone), green tea (epigallocatechins, catechins), and red pepper (capsaicinoids) were tested for their efficacy to control oxidation in pork meat products and it was found that these extracts effectively controlled the lipid oxidation (Yoon et al, 2021).…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…Several authors have reported the antimicrobial and antioxidant effects of EO and oleoresins on meat and meat products [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Al-Hijazen [ 54 ] showed that adding 150 ppm oregano EO + 350 ppm of rosemary extract to ground chicken had the highest antioxidant effect on lipids and proteins [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study exploring the synergistic effect of EO, from herbs and spices, commonly used in meat products, reported that the EO from thyme, garlic, cumin and cinnamon have the lowest minimum inhibitory concentration (MIC); moreover, garlic essential oil inhibited the growth of Salmonella spp., L. monocytogenes and S. aureus [ 55 ]. In addition, rosemary extract power added to cured pork sausages reduced lipid oxidation [ 52 ]. Likewise, BH formulated with shirazi thyme, cinnamon and rosemary extracts had the lower degree of lipid and protein oxidation, as well as better scores on the sensory attributes of BH formulated with these extracts [ 46 ].…”
Section: Introductionmentioning
confidence: 99%